Leakage Sign for Primary Intracerebral Hemorrhage: A Novel Predictor of Hematoma Growth. Issue 4 (April 2016) - Orito, Kimihiko; Hirohata, Masaru; Nakamura, Yukihiko; Takeshige, Nobuyuki; Aoki, Takachika; Hattori, Gousuke; Sakata, Kiyohiko; Abe, Toshi; Uchiyama, Yuusuke; Sakamoto, Teruo; Morioka, Motohiro
Abstract : Background and Purpose—: Recent studies of intracerebral hemorrhage treatments have highlighted the need to identify reliable predictors of hematoma expansion. Several studies have suggested that the spot sign on computed tomographic angiography (CTA) is a sensitive radiological predictor of hematoma expansion in the acute phase. However, the spot sign has low sensitivity for hematoma expansion. In this study, we evaluated the usefulness of a novel predictive method, called the leakage sign. Methods—: We performed CTA for 80 consecutive patients presenting with spontaneous intracerebral hemorrhage. Two scans were completed: CTA phase and delayed phase (5 minutes after the CTA phase). By comparing the CTA phase images, we set a region of interest with a 10-mm diameter and calculated the Hounsfield units. We defined a positive leakage sign as a >10% increase in Hounsfield units in the region of interest. Additionally, hematoma expansion was determined on plain computed tomography at 24 hours in patients who did not undergo emergent surgery. Results—: Positive spot signs and leakage signs were present in 18 (22%) patients and 35 (43%) patients, respectively. The leakage sign had higher sensitivity (93.3%) and specificity (88.9%) for hematoma expansion than the spot sign. The leakage sign, but not the spot sign, was significantly related with poor outcomes (severely disabled, vegetative state, and death) in all of the patients ( P =0.03) and in patients with a hemorrhage in the putamen ( P =0.0016). Conclusions—: The results indicate that the leakage sign is a useful and sensitive method to predict hematoma expansion. Abstract : Supplemental Digital Content is available in the text.